2017
DOI: 10.1002/iid3.173
|View full text |Cite
|
Sign up to set email alerts
|

Increase of cells expressing PD‐1 and PD‐L1 and enhancement of IFN‐γ production via PD‐1/PD‐L1 blockade in bovine mycoplasmosis

Abstract: IntroductionBovine mycoplasma, chiefly Mycoplasma bovis, is a pathogen that causes pneumonia, mastitis, arthritis, and otitis media in cattle. This pathogen exerts immunosuppressive effects, such as the inhibition of interferon production. However, the mechanisms involved in bovine mycoplasmosis have not been fully elucidated. In this study, we investigated the role of the programmed death‐1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) pathway in immunosuppression in bovine mycoplasmosis.MethodsIn the initial expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Then, we hypothesized that this immune dysfunction via PGE 2 -PD-L1 axis is commonly involved in bovine chronic infections. Therefore, this study focused on M. bovis infection, which is known to show immune dysfunction induced by exhausted T cell during the disease progression (11). In this study, we demonstrated that M. bovis induced PGE 2 production from monocytes in line with the upregulation of PD-L1 expression on monocytes (Figures 1A-F).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Then, we hypothesized that this immune dysfunction via PGE 2 -PD-L1 axis is commonly involved in bovine chronic infections. Therefore, this study focused on M. bovis infection, which is known to show immune dysfunction induced by exhausted T cell during the disease progression (11). In this study, we demonstrated that M. bovis induced PGE 2 production from monocytes in line with the upregulation of PD-L1 expression on monocytes (Figures 1A-F).…”
Section: Discussionmentioning
confidence: 69%
“…We previously reported that PD-1/PD-L1 blockade by antibovine PD-1/PD-L1 mAbs enhanced the M. bovis-specific IFN-γ response in vitro (11). Recent research showed that the combined blockade of the PD-1/PD-L1 pathway and PGE 2 by anti-PD-L1 mAb and a COX-2 inhibitor enhanced immune responses against several pathogens (18,19,31).…”
Section: Combined Blockade Of the Pd-1/pd-l1 Pathway And Pge 2 Enhancmentioning
confidence: 99%
See 3 more Smart Citations